Formulasi dan Evaluasi Sediaan Suppositoria Ibuprofen - Naswa Salsabila; Lubna Nurul Mumtazah; Sayna Wahyu Ananta; Adriansyah Adriansyah; Zahra Alatas (Journal of Educational Innovation and Public Health, 2026)
Ibuprofen is an antipyretic and anti-inflammatory drug classified as Biopharmaceutics Classification System (BCS) class II, characterized by low water solubility and high permeability. Its limited solubility may reduce the dissolution rate and influence therapeutic effectiveness. This study aimed to formulate ibuprofen suppositories using cocoa butter (oleum cacao) as the suppository base through the melting method. Each suppository was prepared with a total weight of 2500 mg containing 125 mg ibuprofen, oleum cacao as the base, tween 80 as an emulsifier, and liquid paraffin as a mold lubricant. Before formulation, a displacement value test was performed to determine the exact amount of base required. The prepared suppositories were evaluated through organoleptic examination, weight uniformity, melting time, and dissolution testing. The evaluation results demonstrated that the suppositories possessed acceptable physical characteristics, uniform weight distribution, appropriate melting properties, and satisfactory dissolution behavior. Based on these findings, ibuprofen suppositories formulated with oleum cacao fulfilled pharmaceutical quality requirements in accordance with the Indonesian Pharmacopoeia standards.